Does the superior position of countries in co-authorship networks lead to their high citation performance - Sadatmoosavi, Ali; Nooshinfard, Fateme; Hariri, Nadjla; Mohammad Esmaeil, Sedighe (Malaysian Journal of Library and Information Science, 2018)
The objective of this research was to determine the macro-topological structure and the relationship between citation performance and centrality measures of co-authorship social networks of countries in the field of Nuclear Science and Technology from 2008 to 2010. The present study applied the network analysis method in order to visualize co-authorship networks. Hypothesized relationships were tested using the authors of 24,308 documents cited in the Web of Science. Data relevant to citation performance of a country was based on the articles published by the researchers of the country in a three-year period and the citation data of articles were collected two years after their publication. The investigation of co-authorship social network in the field of Nuclear Science and Technology revealed that the countries which are members of a Nuclear Club hold a prominent position in the network and their influence or power in the network is greater than other countries. Having characteristics like short mean path length, low network diameter (less than or equal to 6) and relatively high clustering coefficient, this network is regarded as a Small World Network. The results of testing the research hypotheses indicated that as the value of centrality of countries rise, the citation performance of researchers in that country is also improved. The analysis of variance confirmed the validity of stepwise regression analysis in predicting the citation performance of researchers (F=816.958 and p>0.000) and through three steps, three components including degree centrality, beta centrality and flow betweenness centrality were concluded to have multiple correlation with citation performance of researchers